Strategi Humas Setda Kabupaten Wonogiri Dalam Menjalin Hubungan Baik Dengan Media - Kinasih, Destika Putri; , Drs.Joko Sutarso, S.E.M.Si (2017)
Government public relations is one of the institutions that are within the realm of public relations duties ureaucracyi. One of the tasks of the government is able toestablish good relations with the mass media in order to support the disclosure ofinformation from the government to the people. Humas Secretariat of Wonogirihas an important role to maintain the loyalty and the public's confidence in the running duties and functions of governance. Media is an external public is themeans of communication between public relations with the public, throughcooperation that the district public relations wonogiri Secretariat can inform thepublic about existing policies in the policy of his government. The purpose of thisstudy to determine what strategies are used public relations in good relations with the media. In this research, using qualitative descriptive method that describes indepth about the strategies used in the realm of public relations Wonogiri districtSecretariat. The technique of collecting data using in-depth interviews (in-depthinterviews), documentation and observation. Media relations strategy is crucialfor Public Relations ecretariat of Wonogiri, one way to develop the programthrough the relationship between public relations with the media. So that theimplementation of the publication and delivery of information to the public aboutgovernment policies can run optimally. The results that have been achieved aswell as public relations, public relations in delivering convenience for thepublication of the policy - district government policies in the media. Besides thecloser personal relationship between public relations related to the cooperationwith the journalist delivery of information to the public. Public Relations StrategySecretariat of Wonogiri in establishing a good relationship with the media is done by continuing to maintain harmony and communicate well.